Economic assessment of water storage in Sub-Saharan Africa - Xenarios, Stefanos; McCartney, Matthew P.; Adenew, B. (2010)
The development of water storage schemes is considered a major aid for agricultural regions in Sub-Saharan Africa with scarce water. The selection of storage options is often conducted through the valuation of direct costs and benefits. Such an approach, based solely on monetary values, often leads to reductionism in the assessment process and loss of valuable information. This in turn can result in less than optimal decision-making. Against this background, this paper proposes an alternative approach based on a range of different criteria. Though based on the underlying principle of economic efficiency, the approach proposed avoids some of the weaknesses of simple cost-benefit analyses. The new approach has been evaluated through application to case studies in Ethiopia.